Gaming behavior and addiction among Hong Kong adolescents - Wong, Irene Lai Kuen (Asian J Gambl Issues Public Health, 2016)
OBJECTIVES: Game playing is very popular among Hong Kong teenagers. This study aimed to investigate adolescent gaming behavior and addiction at the Internet cafe, and to explore perceived benefits and harms associated with the activity. METHODS: A convenient sample of 13 male high school students aged 12–15 years (mean age = 13.6 years) were interviewed at two Internet cafes. Young’s (Caught in the net, Wiley, New York, 1998) criteria of Internet addiction were modified to assess gaming addiction. RESULTS: Internet cafes were described as a safe and ideal rendezvous for gamers. The benefits of gaming included fun and satisfaction, fostering social support and teamwork, meeting new friends and becoming sociable, boosting cognitive techniques and intellectual agility, improved responsiveness and quick thinking. Perceived harms of gaming addiction were reduced time and interest in other important activities, poor academic performance, physical harms and emotional distress, disrupted friendship with non-gaming peers, risked family relationship and financial problems. Five interviewees (38.5 %) could be categorized as pathological gamers and two were problem gamers (15.4 %). The psychological factors associated with gaming addiction include low self-esteem, a strong desire for aggressive and exciting experiences, reliance on gaming to kill time and to obtain satisfaction, coping with problems and negative emotions, and obsession with achieving higher rankings in games. The social and environmental risk factors are accessibility to the Internet cafés, aggressive promotional activities at the Internet cafes, peer pressure, family influence and early gaming experiences, perceived parental approval, lack of parental supervision, and poor family relationship. CONCLUSIONS: The study results throw light on prevention programs.